2019
DOI: 10.1111/tbed.13401
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus spread and differential chemokine response in the central nervous system of mice: Role in pathogenic mechanisms of encephalitis

Abstract: Summary West Nile virus (WNV) is a zoonotic mosquito‐borne flavivirus able to cause severe neurological disease in humans, horses and various avian species. The more severe pathological changes of neurotropic WNV infection are caused by virus neuroinvasion and/or the immunological response in the central nervous system (CNS). The extent in which inflammatory cell trafficking orchestrated by chemokines is involved in the pathogenesis of CNS lesions has not been entirely elucidated. To understand the sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Interestingly, loss of IFN-I signaling resulted in further elevated expression of CCL5 (probably as a compensatory mechanism). Studies conducted with WNV virus infection also shows that increase in cytokine and chemokine response to be part of CNS pathogenesis [26]. IFN-I-independent expression of CXCL-10 in the case of HIV-I infection is shown previously, and our study is in-line with these observations [40].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, loss of IFN-I signaling resulted in further elevated expression of CCL5 (probably as a compensatory mechanism). Studies conducted with WNV virus infection also shows that increase in cytokine and chemokine response to be part of CNS pathogenesis [26]. IFN-I-independent expression of CXCL-10 in the case of HIV-I infection is shown previously, and our study is in-line with these observations [40].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, in another alphavirus, Sindbis virus infection, the Interferon-gamma (IFN-γ) modulates resolution of CNS inflammation by promoting tissue-resident CD8 memory T (T RM ) response while restricting peripheral T cell entry [25]. In a similar line, West Nile fever virus (WNV) infection in a mouse model showed overexpression of proinflammatory chemokines such as CCL2, CCL5, and CXCL10, collectively modulating the immunopathology in the brain [26]. Other than IFN-I, various factors determine the quality of CNS immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Primary means of USUV entry to the brain are still to be determined. The pattern of WNV spread into the CNS may include both hematogenous or neuronal routes [46] and vary according to the route of inoculation [47]. In Vero cells, USUV can establish a persistent infection for at least 80 days [48].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is reinforced by the results of Vielle et al [49], which showed that human respiratory epithelial cells of the nasal cavity are targets for USUV replication in vitro. Intranasal infection of immunocompetent mice with certain WNV strains resulted in fatal encephalitis and death of the animal [47,[50][51][52], and in avian models, bird to bird transmission of WNV was experimentally confirmed [53]. A histopathological study including sections from the nasal cavity epithelium and the CNS (notably the olfactory bulb) at different stages of the infection would be needed to discern lesional patterns compatible with USUV replication in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that microglia are activated during WNV-induced CNS disease in humans includes the presence of microglial nodules and increased proliferation [ 51 , 52 ]. Activated microglia are also seen in the CNS of mice infected with WNV [ 53 , 54 , 55 ] and in WNV-infected ex vivo brain and spinal cord slice cultures [ 21 , 41 ]. The use of ex vivo slice cultures allows for isolation of the CNS immune system from the peripheral immune response.…”
Section: Microglia Become Activated During Wnv Infectionmentioning
confidence: 99%